Prescribing behaviour and challenges in rational antibiotic use at a medical college teaching hospital, Kathmandu, Nepal - Raut, Binod; Pant, Subash; Pradhan, Mazum; Khadka, Anjan (Journal of Chitwan Medical College, 2025)
Introduction: In context of lower-middle income country like Nepal, a considerable proportion of antibiotics are prescribed irrationally, based on availability without proper diagnosis and culture sensitivity test. Thus this study aimed to assess the perception and prescribing practices of medical practitioners regarding antibiotic use. Method: A descriptive cross-sectional study was conducted among 150 medical practitioners, including general physicians, specialists, and residents of a tertiary care teaching hospital from Aug 2024 to Jan 2025 . Convenience sampling was applied to selected sample after obtaining the ethical clearance. Data were collected through self-administered questionnaire assessing demographic details, perception of antibiotic stewardship, prescribing patterns, and attitudes toward antimicrobial resistance. Descriptive statistics were used for analysis. Result: Of the 150 respondents, 87(58%) were above 30 years, and 95(63.4%) were male. Most practitioners 98(65.4%) had less than 10 years of experience. While 124(82.66%) were aware of antibiotic prescribing guidelines. Only 62(41.33%) always prescribed antibiotics after culture and sensitivity tests, and 92(61.33%) preferred prescribing brand-name antibiotics over generic ones. The most commonly prescribed antibiotics were beta-lactams and fluoroquinolones and the most common indication was for respiratory infections. The primary reasons cited for irrational antibiotic prescription included lack of Antimicrobial Stewardship 35(23.33%), limited consultation time 32(21.33%), and inappropriate indication 31(20.67%). Most respondents 37(24.67%) emphasized the importance of regular trainings; continue medical education and workshops for improving prescribing behaviours. Conclusion: The findings highlight improvements in antibiotic prescribing practices and the need for enhanced training programs, stricter adherence to prescribing guidelines, and increased diagnostic accuracy.